Detection and distinguishing infections bursal disease virus (IBDV) strains by molecular biology method - Omar, Abdul Rahman; Mohd, Hair-Bejo; Ideris, Aini; Hamzah, Hairul Aini (2010)
The present invention relates to a novel method to detect and differentiate different strains of infectious bursal disease virus (IBDV) in a chicken and other bird sample. RNA was obtained from said samples by using a pair of primer (Primer FVVC & RVVC) in a reverse transcriptase-polymerase chain reaction. Two different primer combinations (Primer IF & IVIR) and (Primer IF & RCLA) and real-time polymerase chain reaction conditions were designed and optimized for rapid differentiation of very virulent and vaccine strains of IBDV based on detection of signatory threshold cycle (Ct) and melting temperature (Tm) values.